2005
DOI: 10.1007/s10588-005-5587-5
|View full text |Cite
|
Sign up to set email alerts
|

Performance Variability and Project Dynamics

Abstract: We present a dynamical model of complex cooperative projects such as large engineering design or software development efforts, comprised of concurrent and interrelated tasks. The model contains a stochastic component to account for temporal fluctuations both in task performance and in the interactions between related tasks. We show that as the system size increases, so does the average completion time. Also, for fixed system size, the dynamics of individual project realizations can exhibit large deviations fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…Simulation work on the NK model complemented by other models has shown that the decentralized search of interdependent subproblems tends to slow and get bogged down as the problem's complexity (the number of subproblems) increases (Ethiraj and Levinthal 2004, Huberman and Wilkinson 2005, Mihm et al 2003: ongoing choices in some groups make the requirements for other groups inherently unstable (Thomke 1997, Van Zandt 1999. Although these studies have identified managerial actions to mitigate the problem, they have not addressed the question of whether and how hierarchical organizational structures can improve search time and quality.…”
Section: Organizational Hierarchy and Searchmentioning
confidence: 99%
“…Simulation work on the NK model complemented by other models has shown that the decentralized search of interdependent subproblems tends to slow and get bogged down as the problem's complexity (the number of subproblems) increases (Ethiraj and Levinthal 2004, Huberman and Wilkinson 2005, Mihm et al 2003: ongoing choices in some groups make the requirements for other groups inherently unstable (Thomke 1997, Van Zandt 1999. Although these studies have identified managerial actions to mitigate the problem, they have not addressed the question of whether and how hierarchical organizational structures can improve search time and quality.…”
Section: Organizational Hierarchy and Searchmentioning
confidence: 99%
“…In one such model, Loch et al (2003) apply an eigenstructure analysis to show that convergence of an iterative process becomes less probable and more time-consuming as the number of coupled tasks increases. In two others, Huberman and Wilkinson (2005) and Schlick et al (2013) create spectral models incorporating fluctuations in task performance, both showing that variance in overall process time can increase dramatically if the fluctuations exceed a certain threshold.…”
Section: Meso-level Ms/or Modelsmentioning
confidence: 99%
“… is needed to solve complex problems [9];  may help to deal with a changing context [9];  may be reduced by a focus on central information-consuming/generating nodes [2];  is strongly influenced by small changes in task time if close to capacity [10].…”
Section: Literature Reviewmentioning
confidence: 99%